Factors affecting sexuality of elderly people and sexual dysfunctions - Fronc, Kamila; Zielińska, Patrycja; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction: Sexuality of elderly people is often an omitted topic. There isn’t a compact definition of sexuality of seniors. The available data shows that there are many factors influencing sexual activity in later life. There are also specific changes which contribute sexual dysfunctions. Purpose: The aim of present is to investigate what factors are related with decreased sexual activity of seniors, biological basis of sexual dysfunctions and how many elderly people it affects. Materials and methods: There were analyzed publications from 2007 to 2022 from PubMed and Google Scholar using phrases: older adults, elderly people, sexuality of elderly people, factors influencing sexuality, sexual dysfunctions. The state of knowledge: Almost half of people above 60 years old are sexually active. There are factors like low availability of partner, stereotypes, chronic diseases and treatments that contribute worse quality of sexual life. There are reports that communication between doctor and patient on the topic of sexuality is not sufficient, even more positive attitudes towards sexuality of seniors. Biological changes like lower hormone levels in women as well as in men contribute sexual dysfunctions. There are almost one in five women above 57 years old who feel pain during intercourse and there are about 43% of men above 65 with erectile problems. The awareness of sexual dysfunctions could make it easier to treat them. Conclusions: It is essential to pay attention to psychological, social, cultural and attitudes of health professionals towards sexuality of elderly people to diagnose sexual dysfunctions. Understanding biological basis of sexual dysfunction can facilitate matching appropriate treatment. Education can improve seniors’s quality of life and sexual functions.